2023
DOI: 10.1128/spectrum.01906-22
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Gut Microbiota Compositions along the Intestinal Tract in CD163/pAPN Double Knockout Piglets and Their Potential Roles in Iron Absorption

Abstract: Iron deficiency is a major risk factor for iron deficiency anemia, which is among the most common nutritional disorders in piglets. However, it remains unclear how the gut microbiota interacts with host iron absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 60 publications
(73 reference statements)
0
0
1
Order By: Relevance
“…Here we also saw that the relative abundance of Ruminococcaceae_UCG-014 increased in the CMH, suggesting that there was a close relationship between the intake of IONPs and Ruminococcaceae_UCG-014. Zhang et al [67] found that the abundance of Ruminococcaceae_UCG-014 in pigs was negatively 10 correlated with tissue iron levels, which is inconsistent with the present study; this may be due to the different study animals. Bilophila is a genus of lipopolysaccharide (LPS)-producing and mucosadamaging bacteria [68], Marvinbryantia is a characteristic bacteria in the colonic mucosal microbiota [69], and Bifidobacterium can competitively occupy the surface of the intestinal mucosa, preventing the invasion of pathogenic bacteria and reducing the absorption of LPS [70].…”
Section: Discussioncontrasting
confidence: 95%
“…Here we also saw that the relative abundance of Ruminococcaceae_UCG-014 increased in the CMH, suggesting that there was a close relationship between the intake of IONPs and Ruminococcaceae_UCG-014. Zhang et al [67] found that the abundance of Ruminococcaceae_UCG-014 in pigs was negatively 10 correlated with tissue iron levels, which is inconsistent with the present study; this may be due to the different study animals. Bilophila is a genus of lipopolysaccharide (LPS)-producing and mucosadamaging bacteria [68], Marvinbryantia is a characteristic bacteria in the colonic mucosal microbiota [69], and Bifidobacterium can competitively occupy the surface of the intestinal mucosa, preventing the invasion of pathogenic bacteria and reducing the absorption of LPS [70].…”
Section: Discussioncontrasting
confidence: 95%